Bekerja Sebagai Konten Kreator Youtube Menurut Pandangan Islam - Junet Andi Setiawan (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this research is to find out how to work as a YouTube content creator from the perspective of Islamic. This research is a type of field research using a descriptive approach. In this study, data were obtained using observation and documentation techniques. The results of the research explained that working as a YouTube content creator or being a YouTuber is a good job and is permissible in Islam as long as the content created contains things that violate sharia. Then related to whether or not income from adsense/YouTube advertisements is halal is influenced by the content uploaded and the advertisements that appear on the channel. If it does not violate the Shari'a, the income is lawful, but if it violates the Shari'a, the income is illegitimate